Pension Incentives and Labor Force Participation: Evidence from the Introduction of Universal Old-Age Assistance in the UK - Philipp Jäger; Matthias Giesecke (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We estimate the labor force participation (LFP) response to the introduction of means-tested minimum pensions in the UK through the Old-Age Pension Act (OAP) of 1908. The OAP was a major social policy intervention and the first one to universally target older workers in a time of very limited social protection. The empirical framework is based on three decennial census waves (1891, 1901, 1911), covering the full UK population. We identify the LFP effects of the program based on variation at the age-based eligibility threshold between 69 and 70. Our results show a considerable and abrupt decline of 6.3 to 7.6 percentage points in the LFP rate when older men turn 70. This sudden drop only occurs at the age cutoff and only after the OAP was implemented. The unique historical setting allows us to study the full labor supply effects of an old-age assistance program and thus adds to understanding labor supply responses when labor earnings are taxed implicitly through government transfers.
Keywords: H24; H55; J14; J22; J26; 330; Old-Age Assistance; Labor Force Participation; Retirement; Regression Discontinuity Design